Macroeconomics - Gordon, Robert 1935- (Pearson Education Limited, 2014)
Macroeconomics is widely praised for its ability to present theory as a way of evaluating key macro questions, such as why some countries are rich and others are poor. Students have a natural interest in what is happening today and what will happen in the near future. Macroeconomics capitalizes on their interest by beginning with business cycles and monetary-fiscal policy in both closed and open economy. After that, Gordon presents a unique dynamic analysis of demand and supply shocks as causes of inflation and unemployment, followed by a dual approach to economic growth in which theory